Faktor-Faktor Yang Berhubungan Dengan Kejadian Berat Badan Lahir Rendah Pada Ibu Bersalin Di RSUD Kota Depok Tahun 2020 - Situmeang, Irene Florensia; Ningsih, Nurul Syuhfal (Akademi Kebidanan Bunga Husada Samarinda, 2022)
Low Birth Weight is defined by the World Health Organization as a birth weight of less than 2500 grams. The percentage of LBW in West Java province in 2019 was 2.4% with a total of 21,744 of the 920,965 live births, in 2018 it was 2.51% with a total of 22,084 people from 912,298 live births. 2017 was 2.4% with a total of 21,906 people from 915,371 live births. The percentage of LBW in Depok City in 2017 was 1.1% with a total of 475 out of 42,665 live births. The results of this study indicate that there is a relationship between parity, gestational age, anemia and gemelli with Low Birth Weight in Maternal Maternity at the Depok City Hospital in 2020.